Antihypertensive medication prescription patterns and time trends for newly-diagnosed uncomplicated hypertension patients in Taiwan - Liu Pang-Hsiang; Wang Jung-Der (BMC, 2008)
Abstract Background Knowledge of existing prescription patterns in the treatment of newly-diagnosed hypertension can provide useful information for improving clinical practice in this field. The aims of this study are to determine the prescription patterns and time trends for antihypertensive medication in newly-diagnosed cases of uncomplicated hypertension in Taiwan and to compare these with current clinical guidelines. Methods A total of 6,536 newly-diagnosed patients with uncomplicated hypertension, aged ≥30 years, were identified from the representative 200,000-person sample in the computerized reimbursement database of the National Health Insurance in Taiwan. These patients were followed from 1998 to 2004 with all diagnoses, prescription data and medication charges being retrieved for subsequent analysis. Results Prescription patterns varied by age, gender and clinical facilities, with mono-therapies being found to be dominant in the first year, albeit declining over time. Calcium channel blockers and beta-blockers were the most frequently prescribed antihypertensive drugs, either alone or in combinations. Although least expensive, the prescription rates of diuretics were low, at 8.3% for mono-therapies and 19.9% overall. The prescription rate for angiotensin receptor blockers (ARBs) was elevated considerably over time. After controlling for other related factors by multiple logistic regression analysis, ARBs were found to be prescribed mainly by medical centers or regional hospitals. Conclusion These findings indicate the existence of a gap between current clinical practice and the desired goal of cost-effectiveness in antihypertensive treatment in Taiwan, which should be corrected.